2023
DOI: 10.15252/embr.202255835
|View full text |Cite
|
Sign up to set email alerts
|

The phenotype of the most common human ADAR1p150 Zα mutation P193A in mice is partially penetrant

Abstract: ADAR1 -mediated A-to-I RNA editing is a self-/non-self-discrimination mechanism for cellular double-stranded RNAs. ADAR mutations are one cause of Aicardi-Gouti eres Syndrome, an inherited paediatric encephalopathy, classed as a "Type I interferonopathy." The most common ADAR1 mutation is a proline 193 alanine (p.P193A) mutation, mapping to the ADAR1p150 isoform-specific Za domain. Here, we report the development of an independent murine P195A knock-in mouse, homologous to human P193A. The Adar1 P195A/P195A mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…It is noteworthy that the R892H mutant was identified in conjunction with the Z domain mutation P193A. 17,33 It is possible that the presence of both the P193A mutation and a catalytic mutant is necessary to observe a disease phenotype. However, homozygous mice carrying the P193A mutation alone exhibit a normal phenotype.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that the R892H mutant was identified in conjunction with the Z domain mutation P193A. 17,33 It is possible that the presence of both the P193A mutation and a catalytic mutant is necessary to observe a disease phenotype. However, homozygous mice carrying the P193A mutation alone exhibit a normal phenotype.…”
Section: ■ Discussionmentioning
confidence: 99%
“…This is understood when one considers that a histidine at position 892 could maintain a hydrogen bonding contact and, in its protonated form, even a salt bridge with at least one of the adjacent phosphodiesters in the substrate RNA. It is noteworthy that the R892H mutant was identified in conjunction with the Z domain mutation P193A. , It is possible that the presence of both the P193A mutation and a catalytic mutant is necessary to observe a disease phenotype. However, homozygous mice carrying the P193A mutation alone exhibit a normal phenotype. ,, Since our analysis revealed that the R892H mutation alone can substantially disrupt catalysis of adenosine deamination by ADAR1, it is possible that the R892H mutation is the key change leading to disease for the P193A and R892H double mutant found in the AGS patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies recently zeroed in on the role of the Zα domain in innate immune regulation in vivo ( de Reuver et al 2021 , 2022 ; Maurano et al 2021 ; Nakahama et al 2021 ; Tang et al 2021 ; Jiao et al 2022 ). Mice with mutations in the Zα domain typically exhibit mild or no defects and show subtle changes in editing ( de Reuver et al 2021 ; Maurano et al 2021 ; Nakahama et al 2021 ; Tang et al 2021 ; Liang et al 2023 ). Severe detrimental effects are observed only when the AGS-linked Pro193Ala mutation is introduced in the absence of a second Adar1 p150 allele, resulting in a shortened life span for a subset of animals ( Maurano et al 2021 ; Liang et al 2023 ).…”
Section: Beyond A-to-i Editing: the Involvement Of Adar1 In Pkr And Z...mentioning
confidence: 99%
“…Mice with mutations in the Zα domain typically exhibit mild or no defects and show subtle changes in editing ( de Reuver et al 2021 ; Maurano et al 2021 ; Nakahama et al 2021 ; Tang et al 2021 ; Liang et al 2023 ). Severe detrimental effects are observed only when the AGS-linked Pro193Ala mutation is introduced in the absence of a second Adar1 p150 allele, resulting in a shortened life span for a subset of animals ( Maurano et al 2021 ; Liang et al 2023 ). In all mouse models, the observed interferon up-regulation was MDA5–MAVS dependent, with additional involvement of the dsRNA sensors PKR and LGP2.…”
Section: Beyond A-to-i Editing: the Involvement Of Adar1 In Pkr And Z...mentioning
confidence: 99%